2023
DOI: 10.3390/pharmaceutics15102409
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Diagnostics and Drug Discovery against Resistant and Latent Tuberculosis Infection

Christian Shleider Carnero Canales,
Jessica Marquez Cazorla,
André Henrique Furtado Torres
et al.

Abstract: Latent tuberculosis infection (LTBI) represents a subclinical, asymptomatic mycobacterial state affecting approximately 25% of the global population. The substantial prevalence of LTBI, combined with the risk of progressing to active tuberculosis, underscores its central role in the increasing incidence of tuberculosis (TB). Accurate identification and timely treatment are vital to contain and reduce the spread of the disease, forming a critical component of the global strategy known as “End TB.” This review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 121 publications
0
1
0
Order By: Relevance
“…Interestingly, the results showed effective activity against latent MTB, which is beneficial given the specificity of this system. Latent MTB, unlike active MTB, has several survival properties in extreme conditions, allowing it to enter a state of dormancy capable of surviving in the absence of nutrients and oxygen, latent MTB being the most difficult phase of tuberculosis to detect and treat [63]. Recently our laboratory reported that nanoparticulate systems would be capable of eradicating multi-and extremely RIF-resistant MTB through multiple attacks, which would be favorable for future research into nanosystems and the use of conjugation or surface modification to further improve the targeted administration [64].…”
Section: Time-kill Resultsmentioning
confidence: 99%
“…Interestingly, the results showed effective activity against latent MTB, which is beneficial given the specificity of this system. Latent MTB, unlike active MTB, has several survival properties in extreme conditions, allowing it to enter a state of dormancy capable of surviving in the absence of nutrients and oxygen, latent MTB being the most difficult phase of tuberculosis to detect and treat [63]. Recently our laboratory reported that nanoparticulate systems would be capable of eradicating multi-and extremely RIF-resistant MTB through multiple attacks, which would be favorable for future research into nanosystems and the use of conjugation or surface modification to further improve the targeted administration [64].…”
Section: Time-kill Resultsmentioning
confidence: 99%
“…In this environment, naïve CD4 + cells, once stimulated by interleukin-12 (IL-12), differentiate into T helper 1 (TH1) cells, furthering the immune response ( Fig. 2 ) [ [56] , [57] , [58] ].
Fig.
…”
Section: Limitations Of Conventional Therapies In Tb Treatmentmentioning
confidence: 99%
“…The National Tuberculosis Controllers Association and CDC updated treatment guidelines for LTBI in 2020 are: weekly INH plus RFP for three months, daily RIF for four months or daily INH plus RIF for three months, and the alternative regimen is daily INH for six or nine months [ 185 ]. Due to the increasing resistance of LTBI to the above drugs, the development of new drugs and improved treatment options is imminent, and there are many candidates against LTBI in clinical trials, such as sutezolamide, delpazolid, telacebec, OPC-167832, SQ 109 [ 186 ], tafenoquine [ 187 ], and so on. Notably, Rv0467 , encoding isocitrate lyase (ICL), is a drug target for the treatment of latent TB, but there is no ICL inhibitor that has reached clinical trials [ 188 ].…”
Section: Drugs Associated With Dormancymentioning
confidence: 99%